Requirements for maintenance and live weight gain of moose and wapiti calves during winter ... - Cool, N.; Hudson, R.J. (University of Alberta Library, 1996)
Energy requirements of moose (AIces alces) and wapiti (Cervus elaphus) calves were compared from December to February to determine whether metabolic requirements were lower in a boreal-adapted than in a parkland-adapted wild cervid. Eight calves of each species were divided equally into groups given high or low quality diets. Regression of metabolizable energy intake on liveweight gain provided estimates for maintenance and gain. Metabolizable energy requirements for liveweight maintenance were 560 kJ/kg(0.75).d and for gain were 27 kJ/g. Neither value was significantly different between moose and wapiti nor between genders within species. This similariry in winter metabolism and consistency with the interspecies mean suggests that winter metabolic dormancy is not necessarily an important part of a seasonal energetic strategy. The main difference was that moose calves maintained appetite and continued to grow throughout the winter. ...